Analysis of the Implementation of Government Credit Cards (KKPD) in the Management of Petty Cash Funds at the Regional Secretariat of Magelang City: A Policy Implementation Perspective - Putri, Candra Septian Karunia; Aini, Saras Shinta Qurrota (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study analyzes the implementation of the Regional Government Credit Card (KKPD) in the management of petty cash funds at the Regional Secretariat of Magelang City. The primary issue identified is the lack of integration between KKPD transaction records and the Regional Government Information System (SIPD), as well as the complexity of administrative procedures associated with KKPD usage. Employing a qualitative descriptive approach and guided by policy implementation theory, this research conducted in-depth interviews with nine key informants, including finance staff, division heads, and system administrators directly involved in KKPD management. The findings indicate that the KKPD has been fully implemented across all divisions since 2026, offering advantages such as transaction flexibility, convenience in expenditure, and automatic billing recapitulation from the bank. Despite these benefits, challenges persist, notably the complex registration process and continued reliance on manual transaction recording. This study recommends the development of an integrated information system to connect KKPD transactions with SIPD, thereby enhancing efficiency and accountability in public financial management.